The Application of Join Responsibility System for Minimizing the Risk of Credit: Study on Woman Cooperation "Cahaya Pertiwi" Blitar Regency - Farida, Nurul (Journal of Islamic Economics Perspectives, 2019)
The aim of this research is to understand the system of join responsibility for minimizing credit risk. Realizing the active participants can be applied by join responsibility system. Join responsibility has some elements that are able to improve the sense of togetherness among the participants. They are group, obligation, and rule. The local values contained in the join responsibility system are togetherness, honesty meeting, open-minded, and responsibility. Those can change the behavior of the members to be more disciplined, honest, and responsibility about the right and obligation to fill their load on time. The accuracy of the payment time period can minimize credit risk. Therefore, the capital running out of cooperation would be smoother and fast-developing